2000
DOI: 10.1161/01.cir.101.12.1372
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Angiotensin II and Interleukin 6 in Human Coronary Atherosclerotic Plaques

Abstract: Background-Patients with an activated renin-angiotensin system (RAS) or genetic alterations of the RAS are at increased risk of myocardial infarction (MI). Administration of ACE inhibitors reduces the risk of MI, and acute coronary syndromes are associated with increased interleukin 6 (IL-6) serum levels. Accordingly, the present study evaluated the expression of angiotensin II (Ang II) in human coronary atherosclerotic plaques and its influence on IL-6 expression in patients with coronary artery disease. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
339
0
13

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 603 publications
(364 citation statements)
references
References 54 publications
12
339
0
13
Order By: Relevance
“…We therefore hypothesized that activation of PPAR␦ would prominently inhibit atherosclerosis in an AngII, G protein-mediated proinflammatory model of AngII-accelerated atherosclerosis. Indeed, these results may be highly relevant to the accelerated atherosclerosis associated with the metabolic syndrome, in which both adipose and vascular tissue produce AngII, which may lead to RAAS activation (18)(19)(20)(21)(22). We now report that PPAR␦ and RAAS signaling intersect.…”
mentioning
confidence: 61%
“…We therefore hypothesized that activation of PPAR␦ would prominently inhibit atherosclerosis in an AngII, G protein-mediated proinflammatory model of AngII-accelerated atherosclerosis. Indeed, these results may be highly relevant to the accelerated atherosclerosis associated with the metabolic syndrome, in which both adipose and vascular tissue produce AngII, which may lead to RAAS activation (18)(19)(20)(21)(22). We now report that PPAR␦ and RAAS signaling intersect.…”
mentioning
confidence: 61%
“…The IL-6 effect on the cardiovascular system might be mediated via downstream acute-phase proteins (39) or by IL-6 per se. IL-6 stimulates endothelial activation, vascular smooth muscle cell proliferation (40), and leukocyte recruitment (41), thereby contributing to the process of atherosclerotic plaque growth (42) and instability (43). IL-6 mRNA is overexpressed in atheromatous arteries, and IL-6 expression co-localizes with macrophages in areas of plaque rupture (43).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the well-studied VSMCs and macrophages, fibroblasts are also known to inducibly express IL-6 in response to inflammatory cytokines and/or AS [32][33][34][35][36]. Work from our group has shown that IL-6 is a highly inducible gene, a target for direct A-II activation through the ubiquitous NF-κB pathway [32].…”
Section: Discussionmentioning
confidence: 99%